Green finance: the role of financial institutions / Shahiszan Ismail, Nor Azira Ismail and Jamilah Laidin - Ismail, Shahiszan; Ismail, Nor Azira; Laidin, Jamilah (Universiti Teknologi MARA, Kedah, 2024)
The importance of green finance is rising across the global economies (Sachs et al., 2019). In simple terms, green finance refers to financial goods, services, and investment activities that support and promote ecologically friendly projects and businesses. Its principal goal is to shift capital flows to activities and investments that support the transition to lowcarbon, climate-resilient, and ecologically responsible economies (Ozili, 2022a). In economic activities, green finance involves funding initiatives and businesses that benefit the environment or address environmental issues. Such projects often focus on renewable energy, energy efficiency, sustainable infrastructure, waste management, clean transportation, and other environmentally beneficial endeavours. Green finance takes various forms, including green bonds, green loans, green investment funds, and green insurance. Moreover, green finance is thriving globally, with the green finance market potentially worth $2.36 trillion by 2023 (Sean, 2020). One common green finance instrument is the green bond. The US, China, and France are the three largest issuers of green bonds. To qualify, a bond must adhere to criteria on the use of proceeds, have a process for project evaluation and selection, ensure proper management of any proceeds, and offer detailed reporting. In Malaysia, green finance practices took a significant step when Malaysia launched the world's first green sukuk on June 27, 2017. The sukuk can be defined as a green Islamic bond, where the proceeds are used to fund specific environmentally sustainable infrastructure projects, such as the construction of renewable energy generation facilities. Currently, the total outstanding amount of green, social, and sustainability bonds in Malaysia was approximately USD 6.1 billion at the end of June 2022, with private sector issuances leading the way.